Prevention and treatment of disorders in the reproductive activity of animals as a result of the use of pyrethroids in animal husbandry - Salimova Iroda Yunusovna (Periodica Journal, 2022)
The article provides methods of therapy and prevention of reproductive dysfunctions in animals due to the irrational use of modern insectoacaricides.
Keywords: Peritroid; Esfenvalerate; Reproductive Function; Immunomodulator